PENERAPAN HYPNOBIRTHING UNTUK PERSALINAN NORMAL, AMAN DAN MENYENANGKAN - Desy Syswianti; Rosita Alvia; Tri (LP4M STIKes Karsa Husada Garut, 2021)
The level of maternal anxiety has an impact on the length of labor in the first stage. Anxiety and fear can have an impact on the onset of severe pain and result in decreased uterine contractions, so labor takes longer. The purpose of this activity is to reduce the anxiety of pregnant women during childbirth with hypnobirthing therapy. The methods in this activity are: Dividing antenatal classes for pregnant women in the I, II and III trimesters, making implementation schedules, socializing, conducting pretests on Hypnobirthing. By taking anamnesis, determining the distress scale, determining the learning channel and starting the hypnobirthing session, the first session and at the end of the session were given the task of making positive affirmations about pregnancy and childbirth, conducting a posttest on hypnobirthing and providing labor dance techniques and comfort techniques while the mother was in labor observation. Especially for the third trimester class, the endorphin massage method is given to provide comfort and reduce anxiety for pregnant women facing childbirth. Based on the results of the pretest, the average value of pregnant women about hypnobirthing is 35, which means that the knowledge of pregnant women about hypnobirthing is low. After the pretest was carried out, all pregnant women participated in hypnobirthing activities according to gestational age. The conclusion is that after the socialization of pregnant women's knowledge about hypnobirthing increased and attitudes towards hypnobirthing activities became positive, initially they were hesitant and afraid to do hypnobirthing, became enthusiastic about wanting to do it again and anxiety about pregnancy and childbirth decreased after hypnobirthing was carried out.